Hybrid Optimization and TCAD Simulation of Hole Transport and Passivation Layer In Narrow‐Bandgap Perovskite Solar Cells - Huang, Tzu‐Yu; Li, Chien‐Chen; Lai, Yu‐Hsuan; Gao, Xin‐Kai; Huang, Yu‐Chuan; Yang, Chung‐Chi; Wu, Tien‐Lin; Tan, Chih‐Shan (Solar RRL, 2025)
Exploring the compatibility of Poly[(2,4,6‐trimethylphenyl)diphenylamine] (PTAA) with narrow‐bandgap perovskite solar cells, addressing the challenges posed by PTAA's hydrophobic nature. We combined two optimization techniques—phenethylammonium iodide (PEAI) passivation and UV‐Ozone (UVO) treatment—to develop a hybrid approach. Contact angle measurements confirmed improved hydrophilicity, while atomic force microscopy and scanning electron microscopy showed smoother films with fewer defects. X‐ray diffraction revealed enhanced grain size and crystallinity, supporting the benefits of hybrid optimization, particularly when PEAI was applied before UVO treatment. Technology computer‐aided design (TCAD) simulations further validated that the hybrid optimization not only enhanced processing conditions but also boosted the device's overall power conversion efficiency (PCE) by improving band alignment. The results are supported with numerous simulated data, including potential profile, hole density, and recombination rate, hence unveiling the mechanism underlying the enhancement of PCE. This work presents a promising approach for advancing narrow‐bandgap perovskite solar cells, using both experimental and simulated methods to show the impact of passivation, offering higher efficiency and reduced experimental costs. This study investigates the compatibility of poly[ (2,4,6‐trimethylphenyl)diphenylamine] with narrow‐bandgap perovskite solar cells using a hybrid optimization approach combining phenethylammonium iodide passivation and UV‐Ozone treatment. The results show significant improvements in film quality, energy band alignment, and overall device performance. TCAD simulations confirm that the hybrid method enhances efficiency beyond standard single optimization techniques.